Presuppositions in Taglines of Car Advertisements and the Implication to Language of Marketing Strategy - Rizka Sariansyah Nur Ahmad; Mohammad Febryanto (Jurnal Bahasa Inggris Terapan, 2022)
This research is under the pragmatic studies particularly focusing on the use of presuppositions found in 12 newspaper car advertisements. The researcher used descriptive research method because all the data is obtained from the taglines on advertisement displays and is reviewed based on theory of presuppositions. The data sources include newspaper Pikiran Rakyat and Pasundan Express, and the analysis is based on the theory proposed by Yule (1996) about the type presuppositions to find out the types frequently used in the car advertisements. The result shows that there are three types of presupposition used, namely, 7 existential (50%), 2 factive (14.3%), and 5 lexical (35.7%). The type of presupposition mostly used is Existential Presupposition because existential is the assumption that convey the existence of the car.